2016
DOI: 10.1016/j.jpeds.2016.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Diastolic Closing Margin Is Associated with Intraventricular Hemorrhage in Premature Infants

Abstract: Objective To determine if the diastolic closing margin (DCM), defined as diastolic blood pressure minus critical closing pressure, is associated with the development of early severe intraventricular hemorrhage (IVH). Study design A reanalysis of prospectively collected data was conducted. Premature infants receiving mechanical ventilation (n = 185) with gestational age 23–31 weeks had ~1 hour continuous recordings of umbilical arterial blood pressure, middle cerebral artery cerebral blood flow velocity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Several methodologies have been used to assess cerebrovascular reactivity in both term and preterm infants. 36,37 Both transcranial Doppler and NIRS-derived reactivity indices examined the relationship between spontaneous slow wave oscillations (0.003–0.05 Hz) in mean arterial blood pressure (MABP), Doppler flow velocity, 37 cerebral blood volume (CBV) 16 and cerebral oxygenation 3842 in the time domain. Similarly, coherence and gain have been used in frequency domain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several methodologies have been used to assess cerebrovascular reactivity in both term and preterm infants. 36,37 Both transcranial Doppler and NIRS-derived reactivity indices examined the relationship between spontaneous slow wave oscillations (0.003–0.05 Hz) in mean arterial blood pressure (MABP), Doppler flow velocity, 37 cerebral blood volume (CBV) 16 and cerebral oxygenation 3842 in the time domain. Similarly, coherence and gain have been used in frequency domain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The full derivation of the method has been described in detail and validated previously [19]. For each session, the DCM, i.e., diastolic ABP minus CrCP, was calculated as a marker for the risk of developing IVH [13].…”
Section: Methodsmentioning
confidence: 99%
“…29 The corresponding frequency spectrum has one peak corresponding to the heart rate of the infant (110/min) and one peak at low frequency (5-7/min), which represents the observed slow periodic flow oscillations seen in the Doppler velocity curves However, there is increasing evidence that arterial blood pressure is an inadequate measure of cerebral perfusion pressure and CBF in neonates. 30 Furthermore, a recent study using continuous NIRS monitoring 31 found that cerebral oxygenation was lower in infants who developed IVH, and loss of cerebrovascular reactivity was present just before or during the hemorrhage. High-grade fluctuations in the perfusion waveform of the internal cerebral vein has also been shown to be associated with a high incidence of IVH.…”
Section: New Features Obtained With Neodopplermentioning
confidence: 99%